2014
DOI: 10.1186/1472-6947-14-33
|View full text |Cite
|
Sign up to set email alerts
|

A cohort study of a tailored web intervention for preconception care

Abstract: BackgroundPreconception care may be an efficacious tool to reduce risk factors for adverse pregnancy outcomes that are associated with lifestyles and health status before pregnancy. We conducted a web-based cohort study in Italian women planning a pregnancy to assess whether a tailored web intervention may change knowledge and behaviours associated with risks for adverse pregnancy outcomes.MethodsThe study was entirely conducted on the web on a cohort of Italian women of childbearing age. Data collected at bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
48
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 34 publications
(39 reference statements)
5
48
1
1
Order By: Relevance
“…Most of the studies (n = 9, 75%) examined individuals' knowledge of preconception health. [24][25][26][27]29,30,[33][34][35] These studies varied in the type of intervention as well as the topics selected to assess knowledge increase. Examples of knowledge tested include general preconception health, folic acid intake and its effects, types of foods enriched with folate, and risks of smoking and alcohol exposures.…”
Section: 25mentioning
confidence: 99%
See 4 more Smart Citations
“…Most of the studies (n = 9, 75%) examined individuals' knowledge of preconception health. [24][25][26][27]29,30,[33][34][35] These studies varied in the type of intervention as well as the topics selected to assess knowledge increase. Examples of knowledge tested include general preconception health, folic acid intake and its effects, types of foods enriched with folate, and risks of smoking and alcohol exposures.…”
Section: 25mentioning
confidence: 99%
“…In total, 12 studies met the inclusion criteria for our search. [24][25][26][27][28][29][30][31][32][33][34][35] (See the Supplementary file, in the ARTICLE TOOLS section on the journal site.) No additional studies were identified through hand searches of these studies.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations